COMMUNICATION STYLE USTADZ ABDUL SOMAD ON SOCIAL MEDIA - Suryani, Wahidah; Anako, Cindy Meystika (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 18 No 2 (2022), 2023)
This research is to describe the communication style of ustadz Abdul Somad on social media that is viral and liked by students of the Faculty of Ushuluddin and Da'wah. The research uses a descriptive qualitative method to solve the problem investigated by describing the subject/object of research based on facts or the condition of the natural object. In this case, the compiler uses the approach psychology of communication. The research results show that most follow and like Abdul Somad's communication style on social media, and some just like his relaxed, humorous but firm communication style without following it. Then the effects that students get or feel are cognitive effects (additional knowledge), affective effects (emotions, feelings, and attitudes), and behavioral or conative effects (related to behavior).